Adults Learning about Shale Gas Development: Information Sharing, Community Engagement, and Critical Science Literacy - Colleen Shaughnessy; Esther Prins; Margaret Hopkins (Adult Education Research Conference, 2014)
This paper examines how rural adults in a non-formal education class on Marcellus Shale gas development developed and applied critical science literacy. Through expanding their scientific knowledge, adults shifted how they learned about and shared information with others, their relationship with science, and their self-perceptions as scientifically knowledgeable citizens.